Analisis Persepsi Manfaat dan Harga terhadap Minat Beli Melalui Kepercayaan sebagai Variabel Intervening: Studi Kasus pada Konsumen Tiktok Shop di Yogyakarta - Nosya Hestina Wati; Welsa, Henny; Diansepti Maharani, Bernadetta (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the effect of perceived benefits and prices on purchase intention through trust as an intervening variable for TikTok Shop consumers in Yogyakarta. The variables of this study consist of perceived benefits, price, purchase intention, and trust. The sample in this study was 112 respondents who had made purchases at the TikTok Shop. The data collection method used a questionnaire which was distributed using a purposive sampling technique. This study using Data Quality Test, Classical Assumption Test, Multiple Regression Test and Hypothesis Test. The results of this study indicate there is a positive and significant influence of Perceived Benefits on Trust with a significance value of 0.000, there is a positive and significant influence of Price on Trust with a significance value of 0.000, there is a positive and significant influence of Perceived Benefits on Purchase Interest with a significance value of 0.011, there is a positive and significant influence of price on purchase interest with a significance value of 0.000, there is a positive and significant influence of Trust on Purchase Interest with a significance value of 0.008.